PERAN IBU RUMAH TANGGA DALAM PENCEGAHAN PENULARAN COVID-19 DI WILAYAH DUSUN KEPUH WETAN RT 05 RW 3 DESA KALIREJO KECAMATAN KABAT KABUPATEN BANYUWANGI - PUTRI AYU GALUH WULANDARI; HANDY LALA; SUGIANTO HADI (Politeknik Kesehatan Kemenkes Malang (State Health Polytechnic of Malang), 2022)
Background: Covid-19 has limited activities due to government policies that have an impact on all acivities. The government needs the role of the whole community, and mothers have a central role in prevention Subjects and Method: Research using phenomenology with data triangulation conducted in october 2020. Respondents are housewives in RT 05 RW 3 Pakis Kalirejo Permai, Banyuwangi with the main instrument being the researcher himself and supporting interview guides, recording devices, and documentation Results: The mother’s role provides understanding through communication at any time to improve Clean and Healthy Behaviors (PHBS) and Health Protocol (PROKES) support for new living habits requires facilities and infrastructure, other roles are material selection and healthy food management by choosing ingredients from freshness, content, texture, shape, and aroma as well as the management of food ingredients to maintain the benefits of being washed first, when the food is served it need to be convered Conclusion: Doing prevention with the Health Protocol, hand washing facilities/handsanitizer and masks. Before entering the immediately put the clothes in the laundry and clean yourself. Efforts to increase immunity by selecting food ingredients, processing and serving are also considered. The mother’s role un increasing understanding through communication and education such as reminding them to comply with PROKES that is given continously Keywords: The Role of Housewife, Covid-19 Prevention